Maltodextrin recognition by a macrocyclic synthetic lectin. Issue 62 (19th July 2018) - Stewart, Patrick; Renney, Charles M.; Mooibroek, Tiddo J.; Ferheen, Sadia; Davis, Anthony P.
Abstract : This carbohydrate receptor achieves high affinities in water and shows an unusual preference for α-linked maltodextrins. Abstract : A monocyclic "temple" synthetic lectin, with extended electron-rich aromatic surfaces, shows enhanced affinities for carbohydrates in water. The methoxy substituents favour binding to α-linked maltodextrins, against the all-equatorial substrates normally favoured by this family of receptors.